Tinjauan Teoritas Penetapan VAT Threshold di indonesia - Setiadi Alim Lim (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2011)
In designing a VAT, the determination of the threshold magnitude is one keyfactor in successful implementation of VAT. Basically, the determination of thelevel of the threshold by considering the magnitude of administrative costs andcompliance costs compared to tax revenue generated. Some countries such asGhana and Uganda have trouble in the early implementation of VAT due to thelow set of the level of the threshold. Hence the determination of the optimal levelof threshold has become a very important part in supporting the successfulimplementation of VAT. This paper is intended to evaluate the magnitude of thelevel of threshold applied in Indonesia. The analysis showed that the level ofthreshold applied in Indonesia in general its value does not vary much with theresults of calculations using the prevailing theory.